The Creative Economy at Work - Berndt, Christian (DIE ERDE – Journal of the Geographical Society of Berlin, 2013)
There are good reasons to believe that the economy is faster and more volatile than ever before, that firms – the typical organisations of the economy – are dissolving, and that the boundaries between the economy and other societal fields are blurring. The argument developed in this paper is based on the assumption that the turn to creativity is both a response to and a result of these processes. In this context, two interlinked questions are pursued. The first section asks how creativity is organised and managed in the fields considered as making up the creative industries (organising creativity). After this more general discussion, section two engages more directly with the practicalities of creative work. I chose this focus out of conviction that one can only come to terms with the contemporary economy, if one directs the attention to the question of how creativity is mobilised practically (how creativity works).